Postdigital Bystanding: Youth Experiences of Sexual Violence Workshops in Schools in England, Ireland, and Canada - Jessica Ringrose; Debbie Ging; Faye Mishna; Betsy Milne; Tanya Horeck; Kaitlynn Mendes (Behavioral Sciences)
In this paper, we report on creative- and arts-based sexual violence and bystander intervention workshops we developed and researched in England, Ireland, and Canada, through evaluation surveys, observations, and focus group interviews with nearly 1200 young people (aged 13–18). Whist the young people generally reported benefitting from the intervention, in the context of increasing use of digital technologies amongst youth, we explore the context-specific challenges they faced in learning about and being supported through bystander strategies across a wide range of diverse school spaces. We use the term postdigital bystanding to explicitly explore how teen’s digital networks are often connected to the school-based ‘real life’ peer group, in ways that complicate clear distinctions between online and offline, arguing that these postdigital dynamics have not yet been adequately considered in bystanding interventions. We analyse how the intersectional community, cultural, and identity-specific factors in particular schooling environments shape responses to bystanding in postdigital environments, including how factors of sexism, defensive masculinity, elitism, racism, and a reluctance to report digital issues played out in the responses to the workshops. Finally, following young people’s suggestions, we recommend that schools need to cultivate better safety and support strategies for youth in order to make postdigital bystander interventions more responsive and therefore effective in challenging and preventing sexual violence in society.